Projected pain from noxious heat stimulation of an exposed peripheral nerve - A case report - Hoffmann, Tal; Sauer, Susanne; Horch, Raymund E.; Reeh, Peter (European Journal of Pain, 2009)
Distinct sensory properties of unmyelinated axons in the isolated rat sciatic nerve have previously been revealed by measuring stimulated neuropeptide (CGRP) release in response to noxious stimuli. Axonal sensitization to heat by inflammatory mediators has been demonstrated and shown to depend on the heat- and proton-activated ion channel TRPV1. Recently, we have demonstrated in vitro that heat stimulation of nociceptive axons generates ectopic action potential discharge which resembles the heat response of the corresponding cutaneous nerve endings. It remained however, to be established whether adequate axonal stimulation could also generate projected sensations in a conscious human subject. In a singular human trial, the superficial radial nerve (SR) was exposed and stimulated mechanically as well as with noxious cold (3 °C). These stimuli were unable to induce any conscious local or projected sensations. However, controlled radiant heat applied to the nerve resulted in intense slowly adapting burning pain sensations projected into the center of the SR innervation area. No local sensation was reported. Thus, presumably activated nervi nevorum in the sheath of a healthy nerve do not cause conscious sensations, while axons of passage in mid-nerve exhibit a sensory transduction capacity for noxious heat though not for mechanical and cold stimulation. Axonal heat transduction may therefore become a source of ectopic discharge and neuropathic pain when heat threshold drops to body temperature as is the case with peripheral nerve endings in inflamed skin. © 2008 European Federation of Chapters of the International Association for the Study of Pain.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Nervi nervorum; Neuropathy; Nociception; Sensory transduction